Second generation silver(I)-mediated imidazole base pairs - Hensel, Susanne; Megger, Nicole; Schweizer, Kristina; Müller, Jens (Beilstein Journal of Organic Chemistry, 2014)
The imidazole–Ag(I)–imidazole base pair is one of the best-investigated artificial metal-mediated base pairs. We show here that its stability can be further improved by formally replacing the imidazole moiety by a 2-methylimidazole or 4-methylimidazole moiety. A comparison of the thermal stability of several double helices shows that the addition of one equivalent of Ag(I) leads to a 50% larger increase in the melting temperature when a DNA duplex with methylated imidazole nucleosides is applied. This significant effect can likely be attributed to a better steric shielding of the metal ion within the metal-mediated base pair.
Keywords: bioinorganic chemistry; DNA; imidazole; metal-mediated base pairs; nucleic acids; nucleosides